Comparison of different response devices to assess behavioral tendencies towards chocolate in the approach-avoidance task. (1st October 2021) - Wittekind, Charlotte E.; Blechert, Jens; Schiebel, Tanja; Lender, Anja; Kahveci, Sercan; Kühn, Simone
Abstract: Behavioral tendencies in the Approach-Avoidance Task (AAT) have mostly been assessed using a joystick as a response device. In recent years, other hardware devices such as tablets, smartphones, and computer mice have also been used. However, it remains unclear whether different response devices yield similar results and show comparable psychometric properties. The aim of the present study was to assess approach biases towards chocolate with different response devices and to compare their reliability and validity. Forty-five individuals with regular chocolate consumption completed three different AATs (joystick, computer mouse, touchscreen), each comprised of two blocks. In the compatible block of trials, chocolate-related pictures had to be pulled near while object-related pictures had to be pushed away. In the incompatible block of trials, instructions were reversed. Preregistered analyses revealed that participants were faster to pull than to push chocolate-related pictures relative to object-related pictures, indicating an approach bias for chocolate with no significant differences between response devices. Correlations among the three response devices were low to medium. Exploratory analyses revealed that approach biases were moderated by block order such that biases were only present and associated with craving (joystick AAT only) when the incongruent block was completed first. Internal consistencies of the bias score ranged between r SB  = 0.67-0.76. Results of the present study point to the existence of an approach bias to chocolate regardless of response device, albeit each task seems to measure a different aspect of it. Order effects point to specific temporal dynamics in the acquisition of stimulus response (e.g., chocolate-pull) mappings that require further study.